Effect of acute modafinil ingestion on cognitive and physical performance following mental exertion. (7th June 2019) - Rattray, Ben; Martin, Kristy; Hewitt, Alex; Cooper, Gabrielle; McDonald, Warren
Abstract: Objective: Modafinil is a psychostimulant that has been shown to enhance cognitive and physical performance. Given its long half‐life, it may provide operational advantages if it can improve tolerance to the deleterious effects of prolonged mental exertion. Methods: Physically active males ( n  = 13, 23 ± 4 years, peak oxygen consumption 45.3 ± 3.2 ml kg −1  min −1 ) took part in a placebo controlled, double‐blind randomised crossover study to investigate if modafinil could improve cognitive and physical performance following a prolonged period of mental exertion. Results: Overall modafinil improved performance on a task of executive function over time ( p  = .023; η 2  = 0.376) but did not improve subsequent physical endurance performance (mean difference 2.3 ± 11.5%, p  = .50), despite improvement in 10 out of the 13 participants. Task demand was reported as lower with modafinil, although perceptual measures of fatigue and motivation did not consistently improve. Heart rate during submaximal exercise was higher (134 ± 11 vs. 119 ± 14 bpm, p  < .001), and sleep was reduced (5.5 ± 1.4 vs. 7.5 ± 1.4 hr, p  < .001) and less efficient (64 ± 13 vs. 83 ± 9%, p  < .001) compared with placebo. Conclusions: Operationally, modafinil may offer advantages given the established longer half‐life than other psychostimulants, despite the variable response. The impact of higher heart rates and disrupted sleep on performance must also be considered.